2021
DOI: 10.1002/jmv.26973
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 encephalopathy: Clinical and neurobiological features

Abstract: Severe acute respiratory coronavirus 2 (SARS-CoV-2) has been associated with neurological complications, including acute encephalopathy. To better understand the neuropathogenesis of this acute encephalopathy, we describe a series of patients with coronavirus disease 2019 (COVID-19) encephalopathy, highlighting its phenomenology and its neurobiological features. On May 10, 2020, 707 patients infected by SARS-CoV-2 were hospitalized at the Geneva University Hospitals; 31 (4.4%) consecutive patients with an acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 20 publications
(45 reference statements)
2
27
0
4
Order By: Relevance
“…Background slowing is the most dominant EEG signature in various reports. In a cohort of 23 adult patients with COVID-19 encephalopathy, 17 had diffuse background slowing but none had any ictal discharges [10]. Pasiti et al reported a group of 13 adult patients, all of them had mixed theta and delta 4-8 Hz slowing, among them four had consistent bifrontal slowing [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Background slowing is the most dominant EEG signature in various reports. In a cohort of 23 adult patients with COVID-19 encephalopathy, 17 had diffuse background slowing but none had any ictal discharges [10]. Pasiti et al reported a group of 13 adult patients, all of them had mixed theta and delta 4-8 Hz slowing, among them four had consistent bifrontal slowing [16].…”
Section: Discussionmentioning
confidence: 99%
“…Full understanding of the pathophysiological process behind pediatric COVID-19 attributed encephalopathy is lacking, but hematogenous dissemination, direct brain invasion, secondary hypoxic brain injury, angiotensin-converting enzyme dysfunction, autoimmune-mediated neurotoxicity, and inflammatory cascade pathways activation are presumed contributing mechanisms [9]. Interestingly, the majority of patients have elevated CSF protein indicating some degree of blood-brain barrier disruption, but SARS-CoV-2 cannot usually be isolated from CSF [10]. The commonest brain neuroimaging findings are acute and subacute infarcts, leptomeningeal enhancement, microbleeds, and hyperintense signal abnormalities [11].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, EEG studies were also performed in 41.3% of these patients, indicating alterations in 61.9% of them ( Abenza Abildúa et al, 2021 ). However, other smallest studies pointed encephalopathies in lower frequencies, as for example in a retrospective study developed in Geneva, it is reported 4,4% ( Uginet et al, 2021 ). The Spanish registry cited before found viral RNA of SARS-CoV-2 in cerebrospinal fluid (CSF) of patients with encephalitis in only one case ( Abenza Abildúa et al, 2021 ) and the study from Geneve did not find in any of the patient ( Uginet et al, 2021 ).…”
Section: Neurological Clinical Manifestations Of Sars-cov-2 Infectionmentioning
confidence: 94%
“…Als Enzephalopathie wird ein klinisches Erkrankungsbild verstanden, welches sich meist mit einer Kombination aus akuten Aufmerksamkeits‑, Bewusstseins- und Kognitionsstörungen, mit Delir oder Psychose manifestiert [ 47 ]. Bereits erste retrospektive Studien aus der Stadt Wuhan vermerkten Bewusstseinsstörungen (7,5 %) und Verwirrtheit (9 %) zu den häufigen neurologischen Komplikationen bei hospitalisierten COVD-19-Patienten [ 8 ].…”
Section: Erkrankungen Des Zentralen Nervensystemsunclassified